The impact of the great man made river project on Libya's agricultural activities and the environment - Zidan, Adel Mohamed (2007)
Libya is a dry country with very limited water resources. As the population of Libya increases, so does its demand for water. The search for oil in the 1950s and 60s led to the discovery of vast amount of ‘fossil’ water in aquifers underneath Libya’s southern deserts. In 1984, the Libyan government started the largest civil engineering project ever undertaken in the world that was scheduled to complete within twenty years. The project, popularly known as the Great Man Made River Project (GMMRP), when fully completed can supply a total of 6,500,000m³ of freshwater per day to most northern Libya cities bordering the Mediterranean Sea. Eighty percent of this water is allocated for agricultural activities while the remaining is for municipal and industrial purposes. The impact of the availability of this water on the agriculture activities is tremendous and so is the projected consequences on the environment. In light of this, this study, through a questionaire survey, tries to identify such impact on the agriculture town of Abu Sheiba. Findings from the questionery survey indicate that while the impact of the GMMRP project on agriculture activities are very significant so are the concern of the people on its environmental impacts.